Immune Evasion Pathways and the Design of Dendritic Cell-based Cancer Vaccines - Hanks, Brent A. (Discov Med, 2016)
Emerging data is suggesting that the process of dendritic cell (DC) tolerization is an important step in tumorigenesis. Our understanding of the networks within the tumor microenvironment that functionally tolerize DC function is evolving while methods for genetically manipulating DC populations in situ continue to develop. A more intimate understanding of the paracrine signaling pathways which mediate immune evasion by subverting DC function promises to provide novel strategies for improving the clinical efficacy of DC-based cancer vaccines. This will likely require a better understanding of both the antigen expression profile and the immune evasion network of the tumor and its associated stromal tissues.